Freedom and Imagination Trusting Christ in an Age of Bad Faith. - Giere, S. D. (1517 Media, 2023)
Freedom and Imagination recovers faith as the theological heart of the human being's participation in the life of God, and imagination as faith's interpretive lens. Three areas of ministry and life are explored through the imagination of faith: biblical interpretation, proclamation, and Christian freedom.